Pengaruh Pemanfaatan Kecerdasan Buatan (AI) dalam Proses Rekrutmen terhadap Candidate Experience dan Efektivitas Seleksi. - Hartanto Halim; Irawan Budi Utomo, Aceng Abdul Hamid (YUME : Journal of Management, 2025)
In the digital era, the adoption of Artificial Intelligence (AI) has revolutionized various functions of Human Resource Management, especially in the recruitment process. Companies are increasingly leveraging AI for tasks such as automatic CV screening and initial video interviews to enhance efficiency and manage the large volume of applicants. However, behind the promise of efficiency, critical questions arise regarding its impact on candidates' perceptions and experiences, as well as whether the use of AI truly improves accuracy and effectiveness in finding the right candidates.Research Objective: This study aims to empirically analyze the impact of utilizing AI at the CV screening and initial interview stages on (1) candidate experience, measured through perceptions of fairness, transparency, and communication; and (2) selection effectiveness, assessed in terms of speed, screening accuracy, and quality of candidates who advance to the next stage. Methodology: This research employs a mixed-methods approach. Quantitative data was collected through a questionnaire survey distributed to 250 job applicants who had undergone AI-based recruitment processes in Indonesia. The data were analyzed using regression analysis to test the hypotheses. Furthermore, qualitative data were obtained through in-depth interviews with 15 recruitment managers from various companies to understand the organizational perspective on the effectiveness and challenges of AI implementation.Results: The results of the study indicate that the utilization of AI has a dual impact. From the selection effectiveness side, AI significantly speeds up the time-to-screen and improves accuracy in matching candidates' technical qualifications with job requirements. However, from the candidate experience perspective, it was found that the use of AI without personal and transparent feedback negatively correlates with perceptions of fairness and applicant satisfaction. The lack of "human touch" has become a major complaint that could potentially damage the company’s image (employer branding). Implications and Contributions: This research concludes that AI is a powerful tool for optimizing the recruitment process, but its implementation must be balanced with human-centric strategies. The practical implication for companies is the need to design a hybrid recruitment system that integrates the efficiency of AI with empathetic human interactions to maintain a positive candidate experience. Theoretically, this research contributes to the literature on digital human resource management by highlighting the trade-off between technological efficiency and psychological aspects in the modern recruitment process